The Outlook for Arab Gulf Cooperation - Martini, Jeffrey (RAND Corporation, 2016)
This report examines what binds and divides the six Gulf Cooperation Council (GCC) states-Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates-and presents the outlook for the GCC's evolution over the next ten years. The study aims to help policymakers better understand intra-GCC dynamics and prepare for future trends in a region with high stakes for U.S. strategic interests.